Movement Modeling And Learning Formation Through Youtube Video To Improve Students Volleyball Passing Of SMP Negeri 3 Taman Sidoarjo - Santika Rentika Hadi; Hendra Marhendinata (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2020)
The purpose of this study is to improve the learning outcomes under volleyball by using group learning through motion modeling and formation through YouTube videos. The method in this research is Classroom Action Research (CAR). As subjects were students of class VIII-H of SMP Negeri 3 Taman Sidoarjo. The study used a Kemmis and Mc. Taggart, consists of four stages: 1) Action planning, 2) Implementation of actions, 3) observation and 4) reflection. Collecting data using a basic volleyball ball skills test as well as observation of the learning process. The data obtained were analyzed using descriptive techniques based on percentage analysis. Analysis of the data shows the results of pasing learning at the beginning of the cycle of 45.16%, in the first cycle of 61.29% declared complete, then in the second cycle increased by 83.87% declared complete, so the achievements in the second cycle there was an increase of 38.71% compared to the beginning of cycle 1. The results of the analysis showed the completeness of the learning outcomes of passive volleyball game with the application of group learning and YouTube video modeling in the first cycle to the second cycle experienced changes and increased mastery of volleyball pasing learning both individually and classially.